Pastoralism Development in the Sahel : A Road to Stability? - De Haan, Cees; Dubern, Etienne; Garancher, Bernard; Quintero, Catalina (World Bank, Washington, DC, 2016)
The World Bank’s Global Center on Conflict, Security, and Development, currently the Fragility, Conflict, and Violence Cross-Cutting Solutions Area (FCV CCSA), in 2014 commissioned this note to enhance understanding of the connection between pastoralism and the recent increase in instability and violence in the Sahel, as well as the conditions under which the development of the pastoralist economy can actually enhance regional stability. The note seeks to offer guidance to international, national, and local decision makers on the drivers of conflict and instability that are most related to pastoral communities, as well as possible measures to reduce violence and enhance stability in the Sahel.